Phoenix in Guillermo Reyes’s Places to Touch Him - Foster, David William (Latin American Theatre Review, 2010)
Guillermo Reyes is one of the most important contemporary Chicano dramatists,as much for his ingenious use of language as for his perceptive and unflinching treatment ofgay male culture as it affects Chicano men. Reyes is particularly attuned to the urban cultureof the American Southwest, and the bulk of his plays focuses on the urban implications ofChicano life, which include issues of gay life. While the majority of Reyes’s plays are set inLos Angeles, which has experienced in recent decades an important accommodation of visiblegay life, Reyes’s 2002 play, Places to Touch Him, is situated in the greater Phoenix area, whereReyes lives. Phoenix, while it has a measure of visible gay life, presents significant differencesrelative to Los Angeles, and this is no more apparent than in the matter of political fortunes foropenly gay men (and women). This article discusses how Places engages with the particularparameters of gay life in a U.S. city like Phoenix. (DWF, Article in English)